Recurrent Tracheal Schwannomas: A Case Report and Literature Review - Rakhesh Mallesh; M. M. Zameer; Vinay Chandrashekar; Sanjay Rao (Journal of Indian Association of Pediatric Surgeons)
Tracheal schwannomas are rare benign tumors in pediatric age group. We report a case of recurrent distal tracheal tumor in a 12 year old boy successfully managed with resection under cardiopulmonary bypass and review the relevant literature.